Effects of various aging modes on the optical properties of zirconia with different yttria concentrations in coffee and tea - Chih-Wei Tseng; Chenmin Yao; Liang-Yu Wei; Pei-Wen Peng; Wei-Chun Lin (Journal of Dental Sciences, 2025)
Background/purpose: The esthetic performance of dental zirconia may be affected by both material composition and environmental exposure. This study aimed to evaluate how different aging conditions-hydrothermal aging and thermal cycling-influenced the optical properties of dental zirconia containing varying yttria concentrations (3Y-TZP, 4Y-TZP, and 5Y-TZP) in coffee and tea. Materials and methods: A total of 120 zirconia specimens were prepared using three yttria concentrations. Each group was subjected to four artificial aging conditions: storage in coffee or tea at 37 °C for 1 and 6 months (hydrothermal aging), or 10,000 and 50,000 cycles of thermal cycling between 5 °C and 55 °C. Optical parameters (L∗, a∗, b∗) and color differences (ΔE00) were measured using a spectrophotometer and calculated using the CIEDE2000 formula. Data were analyzed using ANOVA and Tukey's HSD test (α = 0.05). Results: Zirconia with higher yttria content exhibited more pronounced color changes (P < 0.001). Aging in tea resulted in minimal color variation regardless of yttria content or aging mode. In coffee, the ΔE00 values of the HT (3Y-TZP), ST (4Y-TZP), and XT (5Y-TZP) groups ranged from 3.5, 7.0 and 8.5, respectively (P < 0.0001). In tea, the values ranged from 1.1 for both HT and ST, and from 3.1 for XT (P < 0.0001). Conclusion: Both yttria concentration and aging conditions significantly influenced the color stability of zirconia. Hydrothermal aging had a greater impact than thermal cycling, especially in coffee. These findings suggest that material composition and exposure environment should be carefully considered when selecting zirconia for esthetic dental restorations.